2020
DOI: 10.1055/s-0039-1700830
|View full text |Cite
|
Sign up to set email alerts
|

Descontaminação transoperatória de enxerto durante cirurgia de reconstrução do LCA

Abstract: Objective To evaluate different decontaminants for tendon grafts, proposing an antiseptic protocol for contaminated grafts. Methods A total of 25 patients were tissue donors for the study. Each participant donated a 2.5-cm tendon sample, which was divided into 5 fragments with 5 mm each during anterior cruciate ligament (ACL) reconstruction surgery. The collected material was divided into 5 groups, totaling 125 samples. In total, four fragments of each patient were placed on the operating room floor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Several studies have shown an elevated risk of infection using allografts for ACLR [11, 12], to which graft contamination could be an important contributor. Most relevant studies have evaluated accidental contamination, such as dropping on the floor and decontamination methods, such as irrigation, mechanical agitation, or soaking with disinfection solution [3, 6, 25, 28, 33, 36]. However, limited number of studies have focussed on the potential risk of contamination during normal preparation of the graft [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown an elevated risk of infection using allografts for ACLR [11, 12], to which graft contamination could be an important contributor. Most relevant studies have evaluated accidental contamination, such as dropping on the floor and decontamination methods, such as irrigation, mechanical agitation, or soaking with disinfection solution [3, 6, 25, 28, 33, 36]. However, limited number of studies have focussed on the potential risk of contamination during normal preparation of the graft [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…As little as a 15-minute exposure to 10% PVP-I was found to kill 100% of human fibroblasts, and a low concentration of 1% PVP-I was toxic as well. 5 Luciano et al 6 evaluated different decontaminants for tendon grafts. They found that intraoperative graft decontamination is possible using 0.5% chlorhexidine with a rate of 100% decontamination.…”
Section: Introductionmentioning
confidence: 99%